Stroke at a Young Age: Could a Simple Folate Deficiency Be the Cause? - Faiza ,; Gilani, Fatima; Bilal, Yasir; Sarosh, Muhammad; Ali, Baria; Shahid, Muhammad Nauman; Ali, Syed Talal (Pakistan Journal of Medical & Health Sciences, 2025)
Folate deficiency can significantly increase the risk of stroke by elevating serum homocysteine levels, a risk factor that is often underrecognized in younger patients. We report the case of an 18-year-old male who presented to the emergency department with acute right-sided weakness, slurred speech, and facial drooping. Notably, the patient had no history of smoking, hypertension, or other conventional cerebrovascular risk factors. Laboratory evaluation revealed markedly elevated homocysteine levels, implicating underlying folate deficiency as a primary contributor. In the absence of deep vein thrombosis, drug abuse, or other common etiologies, this case highlights the critical role of folate status in stroke risk and underscores the importance of considering metabolic factors in young, otherwise healthy individuals presenting with ischemic stroke.